Deciphering an extreme morphology: bone microarchitecture of the hero shrew backbone (Soricidae: Scutisorex). Issue 1926 (13th May 2020) - Smith, Stephanie M.; Angielczyk, Kenneth D.
Abstract : Biological structures with extreme morphologies are puzzling because they often lack obvious functions and stymie comparisons to homologous or analogous features with more typical shapes. An example of such an extreme morphotype is the uniquely modified vertebral column of the hero shrew Scutisorex, which features numerous accessory intervertebral articulations and massively expanded transverse processes. The function of these vertebral structures is unknown, and it is difficult to meaningfully compare them to vertebrae from animals with known behavioural patterns and spinal adaptations. Here, we use trabecular bone architecture of vertebral centra and quantitative external vertebral morphology to elucidate the forces that may act on the spine of Scutisorex and that of another large shrew with unmodified vertebrae ( Crocidura goliath ). X-ray micro-computed tomography (µCT) scans of thoracolumbar columns show that Scutisorex thori is structurally intermediate between C. goliath and S. somereni internally and externally, and both Scutisorex species exhibit trabecular bone characteristics indicative of higher in vivo axial compressive loads than C. goliath. Under compressive load, Scutisorex vertebral morphology is adapted to largely restrict bending to the sagittal plane (flexion). Although these findings do not solve the mystery of how Scutisorex uses its byzantine spine in vivo, our work suggests potentially fruitful new avenues of investigation for learning more about the function of this perplexing structure.